ANALISIS PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP PEMILIHAN MEREK LAPTOP MENGGUNAKAN REGRESI LOGISTIK MULTINOMIAL (Studi Kasus Mahasiswa Universitas Diponegoro) - Himmah, Faiqotul; Wuryandari, Triastuti; Hoyyi, Abdul (MEDIA STATISTIKA, 2012)
One of necessity is considered very important in this era is necessity for information. The tools that  support necessity of comsumer   for information, such as computer that use battery or better known as laptop. Laptop is a product often used by businessman/enterprise and academic actors also the student are no  exception. There are many laptop brands that revolve in Indonesia, are the Acer brand, Toshiba, Hp, Axioo, Dell, and the brand in addition to those brands. This research aim to know the effect of marketing mix  strategy, which consist of three variable factors: product, price, and promotion to the selection of laptop brand  in  Diponegoro  University  students.  The  sample  of  research  taken  by  using  non probability   sampling,  that  is  purposive  sampling  technique  dan  accidental  sampling technique. Analysis that used is multinomial logistic regression analysis, a regression analysis to  solve  problems  where  dependent  variable  has  more  than  2  categories  with  several independent variables. Based on the significance test for the overall model and the wald test for each parameter coefficient, consider that three of the marketing mix  variables has a relationship with the selection of laptop brand. The biggest probability estimates for the Acer brand in the group with medium product, high price, and high promotion in the amount of 77.461%. The biggest probability estimates for the Toshiba brand in the group with highproduct,  high  price,  and  medium  promotion  in  the  amount  of  49.239%.  The  biggest probability estimates for the Hp brand in the group with medium product, medium price, and medium promotion in the  amount of 46.074%. The biggest probability estimates for the Axioo-Dell brand  in the group with with  medium product,  medium price,  and  medium promotion in the amount of 14.764%. The biggest probability estimates for the other brands in the group with medium product, high price, and medium promotion in the  amount of 22.134%.